1996
DOI: 10.1007/bf00042231
|View full text |Cite
|
Sign up to set email alerts
|

Thi1, a thiamine biosynthetic gene inArabidopsis thaliana, complements bacterial defects in DNA repair

Abstract: An Arabidopsis thaliana cDNA was isolated by complementation of the Escherichia coli mutant strain BW535 (xth, nfo, nth), which is defective in DNA base excision repair pathways. This cDNA partially complements the methyl methane sulfonate (MMS) sensitive phenotype of BW535. It also partially corrects the UV-sensitive phenotype of E. coli AB1886 (uvrA) and restores its ability to reactivate UV-irradiated lambda phage. It has an insert of ca. 1.3 kb with an open reading frame of 1047 bp (predicting a protein wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
93
0
15

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 47 publications
2
93
0
15
Order By: Relevance
“…This suggests that plants may utilize a biosynthetic pathway that is similar to that of microorganisms. Two genes involved in thiamine biosynthesis have so far been cloned and characterized in Arabidopsis [28][29][30]. The first one is THI1, which is involved in thiazole synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that plants may utilize a biosynthetic pathway that is similar to that of microorganisms. Two genes involved in thiamine biosynthesis have so far been cloned and characterized in Arabidopsis [28][29][30]. The first one is THI1, which is involved in thiazole synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is THI1, which is involved in thiazole synthesis. THI1 was isolated by complementation of the E.coli mutant strain BW535, a mutant with defective DNA base excision repair pathways [28]. Further characterization showed that THI1 has two functions: it is involved in the thiazole synthesis of the thiamine biosynthesis pathway and in DNA repair [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the AtXPB (the letters At indicate A. thaliana) gene is homologous to the human XPB gene, which is involved in DNA repair and transcription (Ribeiro et al, 1998). The A. thaliana thi1 gene is homologous to the yeast thi4 gene and seems to be involved in thiamine biosynthesis and mitochondrial DNA damage tolerance (Machado et al, 1996;Machado et al, 1997). The AtMMH gene is homologous to the E. coli mutM gene, which encodes for a glycosylase that recognizes some types of oxidative deoxyguanosine dam-age (Ohtsubo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Em Arabidopis thaliana, o gene thi1 está relacionado com a via da biossíntese de tiamina, sendo composto por uma ORF de 1047 pares de bases, e codifica uma proteína de 349 resíduos de aminoácidos (9). A dedução da sequência polipeptídica da proteína THI1 revelou um alto grau de identidade com as proteínas envolvidas na biossíntese de tiamina em Saccharomyces cerevisiae (51,7% de identidade) e Schizosaccharomyces pombe (55,1% de identidade) (10).…”
unclassified